Ewolucja systemu zabezpieczenia społecznego ludności chłopskiej w Polsce - Kasperek-Hoppe, Maria (Wydział Prawa i Administracji UAM, 1985)
The population engaged in the individual farming was included in the system social security as the last socio-professional group. The Act of Pensionary Rights of Individual Farmers handing over their farms to State ownership or management of June 28, 1962 became an important event. But the exhaustive regulation of the social security was instituted by the Act of Social Security for Farmers and their Families of December 14, 1982. Ensuring the social security to those farmers and their families who on account of various factors are not able to manage their farms is the basic function of the new Act. Revalorisation of farmers pensions is the essential solution introducted in that aspect. The said Act can create potential requisites to stimulate structural changes in individual farming and also institutes solutions which can, in future affect the productivity of individual farms. Reservations can be raised as to the questions of relating a competence to receive a pension from handing over the farm. Benefits should result from the age and period of work and not from the fact of handing over the farm. The adopted solution is hampering becoming independent by young people. It is one of the problems which has to be returned to in the future.
Evolution of the social security system for the peasant population in Poland